Gene structure of the murine calcium channel β3 subunit, cDNA and characterization of alternative splicing and transcription products - Murakami, Manabu; Wissenbach, Ulrich; Flockerzi, Veit (EJB, 1996)
The β3 subunit of high-voltage-gated calcium channels is a peripheral membrane protein that copurifies with neural N-type calcium channels. Murine genomic clones containing the full coding sequence of β3 were isolated and the exons were mapped and sequenced. The murine calcium channel β3 subunit is encoded by a unique gene composed of 13 translated exons that spread over ≈8 kb of genomic sequence. Alternatively spliced transcripts of the β3 gene were identified and characterized. The primary structure of β3 is highly conserved between the murine, human, rabbit and rat proteins (98% identity). The intron placement within that primary structure correlates with the previously postulated exon positions in transcripts encoding the members of the calcium channel β subunit family and confirm a close evolutionary relationship of the β3, β1, β2 and β4 subunit genes.